Dari Guru-Laghu ke Pedhotan: Upaya Menafsirkan Perubahan Metrum Kakawin Menjadi Sekar Ageng - Yudhistira, Naufal Anggito (Manuskripta, 2023)
Sekar ageng or kawi miring is one of the type of Javanese chanted poetry that was arose in the Surakarta-Yogyakarta literature era. This type of poetry is a continuation of the kakawin tradition of Old Javanese literature. However, there is a dark gulf between the emergence of the sekar ageng and the end of the kakawin tradition in Java. This study seeks to reveal the relationship between kakawin and sekar ageng and the transformation of kakawin's poetry prosody into sekar ageng. This study adheres to structuralism which departs from the linguistic aspect. Because this study examines the metre of the poetry that should be chanted, in addition to the linguistic element, it is also associated with the musical element. From this research, it can be seen that sekar ageng was well known in the era of Mataram Islam and was a continuation of the kakawin tradition. The pedhotan element is closely related to the location of the kakawin long syllables. Kakawin syllables are crystallized in musical aspect and syllabic-melismatic syllables in sekar ageng. In terms of sasmitaning tembang, sekar ageng is influenced by the kakawin tradition as well as macapat. === Sekar ageng atau kawi miring adalah salah satu jenis puisi Jawa bertembang yang yang hidup di era kesusastraan Surakarta-Yogyakarta. Jenis puisi ini merupakan kelanjutan tradisi kakawin dari kesusastraan Jawa Kuna. Walau begitu, ada suatu jurang gelap antara kemunculan sekar ageng dan akhir tradisi kakawin di Jawa. Penelitian ini berusaha mengungkapkan hubunganantara kakawin dan sekar ageng serta transformasi prosodi puisi kakawin menjadi sekar ageng. Penelitian ini berpegang pada strukturalisme yang bertolak dari aspek kebahasaan. Oleh sebab penelitian ini mengkaji metrum puisi yang bertembang, maka selain unsur kebahasaan juga mengkaitkan dengan unsur musikalnya. Dari penelitian ini dapat diketahui bahwa sekar ageng sudah dikenal di era Mataram Islam dan merupakan kelanjutan tradisi kakawin. Unsur pedhotan terkait erat dengan letak suku kata panjang kakawin. Panjang-pendek suku kata kakawin terkristalisasi dalam unsur seni suara dan suku kata silabismelismatis yang ada dalam sekar ageng. Dari segi sasmitaning tembang, sekar ageng dipengaruhi tradisi kakawin juga macapat.